2017
DOI: 10.1093/jnci/djx136
|View full text |Cite
|
Sign up to set email alerts
|

The Balance Between Cytotoxic T-cell Lymphocytes and Immune Checkpoint Expression in the Prognosis of Colon Tumors

Abstract: ICK expression cancels the prognostic relevance of CTLs in highly immunogenic colon tumors and predicts a poor outcome in MSI CRC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 31 publications
1
67
0
2
Order By: Relevance
“…Thus, our results are in line with and extend those of Galon et al who clearly demonstrated that a subgroup of MSS CRC exhibits a high Th1/Tc1/IFNγ gene signature, as the majority of MSI CRC. 11,18,38 Moreover, we recapture the favorable prognostic impact of this Th1/Tc1/ IFNγ gene signature in MSI as well as in MSS CRC by quantifying the density of Tbet+ TILs. The identification of Tbet+ TILs by immunohistochemistry was previously reported in CRC in only few studies, with a higher density in MSI than in MSS CRC in line with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results are in line with and extend those of Galon et al who clearly demonstrated that a subgroup of MSS CRC exhibits a high Th1/Tc1/IFNγ gene signature, as the majority of MSI CRC. 11,18,38 Moreover, we recapture the favorable prognostic impact of this Th1/Tc1/ IFNγ gene signature in MSI as well as in MSS CRC by quantifying the density of Tbet+ TILs. The identification of Tbet+ TILs by immunohistochemistry was previously reported in CRC in only few studies, with a higher density in MSI than in MSS CRC in line with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed the lymphocyte infiltration response to the tumour. Increased lymphocytic reactions have been associated with a better outcome [18]. In addition, platelets could secrete cellular growth factors such as platelet-derived growth factor, vascular endothelial growth factor, transforming growth factor β, and platelet factor 4, followed by the stimulation of tumour angiogenesis and growth [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, CTLs recognize tumor cells through tumor-specific antigens to mount an antitumor immune response and suppress tumor progression. However, tumor cells often mount a counterattack by multiple mechanisms including loss of antigen expression, and both primary and acquired resistance mechanisms, which in turn shut down the tumor-reactive CTLs in the tumor microenvironment (13)(14)(15)(16). Therefore, tumor cells hijack the corepressive receptor-based immune checkpoint mechanism to suppress tumor-reactive CTLs to avoid immune rejection (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%